Manajemen Asuhan Kebidanan Pada Remaja Nn "A" dengan Dismenorea Primer di Pesantren Guppi Samata Tahun 2022: Management of Midwifery Care for Adolescent Ms. "A" with Primary Dysmenorrhea at the Guppi Samata Islamic Boarding School - Fera Mirnawati; Anieq Mumthi’ah Al Kautzar; Andi Dian Diarfah (Jurnal Midwifery, 2023)
Introduction. Dysmenorrhea is characterized by severe and frequent cramps and pain during menstrual period. This pain could exist from the first day of the menstruation to several days of the period. Dysmenorrhea is mostly caused by contraction of the uterine wall when an increase in the hormone prostaglandin occurs which helps the process of releasing the uterine wall. This process causes cramps and pain mostly felt by women in the lower abdomen and back. Purpose of this research was to investigate the midwifery care management for an adolescent with the case of primary dysmenorrhea at Guppi Islamic Boarding School of Samata Method The study was conducted by utilizing a 7-stage of Varney management approach. Result of this study, investigating the case of Ms “A”, indicated that the initial treatments for the patient with primary dysmenorrhoea could be in the forms of compressing the lower abdomen using warm water and administering drug therapy. Moreover, it is also important to conduct a follow-up care and medication. Conclusion This study concluded that this study was conducted by implementing the 7-stage of Varney management approach and SOAP documentation procedure. It revealed that 3 home visits were conducted for the patient. In general, it is apparent that the patient was in good condition where the pain could be reduced, and psychological issues encountered by the patient could be overcome